PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE PAIR CHECKS BERBANTUAN APLIKASI SCHOOLOGY TERHADAP PENINGKATAN HASIL BELAJAR SISWA - Lustiana Sari; Dwi Sulisworo (Universitas Muhammadiyah Semarang, 2018)
This research is a quasi-experimental research and research design used is pretest post-test control group design. This study aims to determine the outcomes of learning physics by learners who taught conventionally, to determine the outcomes of learning physics by learners who the taught cooperative learning model type pair checks and to determine significant difference between the result of physics learning by learners who taught in a conventional and are taught by cooperative learning model type pair checks. The sample of this study were 48 students, consist of 24 students in the experimental class and 24 students in the control class. The average value of the experimental class students is 84.58. For the average value of the control, class students are 80.33.The results of the analysis carried out by using the t-test obtained t value of 4.2 with Sig. (2-tailed) of 0,000 with a significant level of 5%. Therefore the value of Sig. (2-tailed) <0.05, it can be said that there are significant differences in physics learning outcomes between the control class and the experimental class that use the cooperative learning model type pair checks. Keywords: pair checks, conventional learning, learning outcomes, Schoology